Effect of cloud microphysics on Indian summer monsoon precipitating clouds: A coupled climate modeling study. Issue 7 (6th April 2017) - Hazra, Anupam; Chaudhari, Hemantkumar S.; Saha, Subodh K.; Pokhrel, Samir
Abstract: The quest for one of the most dominant processes controlling the large‐scale circulations in the tropics is unraveled. The impact of cloud microphysical processes is known to have effects on rainfall and local atmospheric thermodynamics; however, its effect on the prevailing mean circulations is not yet studied. Two sets of coupled global climate model experiments (ICE and NO ICE microphysics) reveal that ice microphysics improves the strength of the Hadley circulation with respect to observation. Results pinpoint that ICE simulation enhances high cloud fraction (global tropics: 59%, India: 51%) and stratiform rain (global tropics: 5%, India: 15%) contribution. ICE and NO ICE cloud microphysics impacts differently on the outgoing longwave radiation (OLR), tropospheric temperature, and surface shortwave and longwave radiation. The effect of ice microphysics reduces OLR, which signifies deeper convection in the ICE run. The global annual average of the net radiation flux (shortwave and longwave) at the surface in ICE run (108.1 W/m 2 ) is close to the observation (106 W/m 2 ), which is overestimated in NO ICE run (112 W/m 2 ). The result of apparent heat source term over the land and ocean surface eventually modifies regional Hadley circulation. Thus, the effect of ice microphysics in the global coupled model is important not only because of microphysics but also due to the radiation feedbacks. Therefore, better ice‐phase microphysics is required in the new generation of climate forecast model, which may lead to improvements in the simulation of monsoon. Key Points: The ice cloud microphysics is important in coupled climate model for the simulation of Indian summer monsoon Hadley circulation, apparent heat source, and radiative fluxes are also modulated by ice‐phase microphysics Fifty percent of the high cloud fraction and 15% of stratiform rain increase in ICE as compared to NO ICE run